Strengthening The Existing Indonesian Government Policies Related to MSMEs to be Sustainable - Lutfi Abdul Khakim; Amrie Firmansyah (Research Synergy Foundation, 2023)
Micro, Small, and Medium Enterprises (MSMEs) was considered the savior in the Indonesian economic crisis 1997 because of their agility to be owned by anyone who intends to do business. On the other hand, MSME faces the threats of limited capital and low-quality human resources. Initially, the effect of the threats was that MSMe caused environmental issues in the surroundings because of the law control management; thus, related research needs to be conducted. This study aims to evaluate the adequacy of the regulatory ecosystem related to MSMEs in Indonesia related to sustainability issues. With this aim, the qualitative descriptive method is very relevant to the needs of this research. The results of this study show that Indonesia's MSME regulatory ecosystem is still weak in raising sustainable issues. Practices to improve sustainability performance were identified, and suggestions to related institutions were also presented at the end of the writing. Research about the adequacy of government policies related to the sustainability of MSMe in Indonesia is infrequently conducted; thus, this research will contribute both academically and practically.